A second Scirtothrips species with a hind-femoral comb in males (Thysanoptera, Thripidae) - Mound, Laurence A. (Zootaxa, 2010)
Amongst the 100 described species worldwide of the genus Scirtothrips, the South African Citrus Thrips, S. aurantii Faure, has been considered unique because the males possess a comb of stout setae on the hind femora (Hoddle & Mound, 2003). A new species that shares this character state is described here from Cedrus (Pinaceae) in Kenya, although no information is available for either species concerning the functional significance of this comb.